Whole-Genome Sequence of a Brucella pinnipedialis Sequence Type 54 Strain Isolated from a Hooded Seal ( Cystophora cristata ) from the North Atlantic Ocean, Norway - Zygmunt, Michel S; Vergnaud, Gilles; Cloeckaert, Axel (Microbiology Resource Announcements, 2021)
International audience Since the 1990s, Brucella strains have been isolated from a wide variety of marine mammal species. We report the first complete genome sequence of a Brucella strain isolated from a hooded seal ( Cystophora cristata), Brucella pinnipedialis strain 23a-1 of sequence type 54, found in the North Atlantic Ocean surrounding Norway.